2020
DOI: 10.1007/s10071-020-01348-5
|View full text |Cite
|
Sign up to set email alerts
|

Perception of dynamic facial expressions of emotion between dogs and humans

Abstract: Facial expressions are a core component of the emotional response of social mammals. In contrast to Darwin's original proposition, expressive facial cues of emotion appear to have evolved to be species-specific. Faces trigger an automatic perceptual process, and so, inter-specific emotion perception is potentially a challenge; since observers should not try to "read" heterospecific facial expressions in the same way that they do conspecific ones. Using dynamic spontaneous facial expression stimuli, we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 67 publications
1
63
1
1
Order By: Relevance
“…While equivocal, accumulating evidence is demonstrating that humans and dogs are uniquely attuned to one another's facial expressions to the exclusion of other domestic mammals (Albuquerque et al, 2016;Schirmer, Seow, & Penney, 2013;Waller et al, 2013). Not only are humans good at reading facial expressions of dogs, but dogs are good at reading facial expressions of humans (Correira- Caeiro, Guo, & Mills, 2020). Does this mutual ability to read one another's facial expressions indicate that dogs and humans co-evolved and influenced one another's brain evolution?…”
Section: F I G U R E 1 Domestication Of Wild Mammals Into New Speciesmentioning
confidence: 99%
“…While equivocal, accumulating evidence is demonstrating that humans and dogs are uniquely attuned to one another's facial expressions to the exclusion of other domestic mammals (Albuquerque et al, 2016;Schirmer, Seow, & Penney, 2013;Waller et al, 2013). Not only are humans good at reading facial expressions of dogs, but dogs are good at reading facial expressions of humans (Correira- Caeiro, Guo, & Mills, 2020). Does this mutual ability to read one another's facial expressions indicate that dogs and humans co-evolved and influenced one another's brain evolution?…”
Section: F I G U R E 1 Domestication Of Wild Mammals Into New Speciesmentioning
confidence: 99%
“…facial expression length is context-dependent [ 23 ]). Researchers have also used the DogFACS alongside HumanFACS to investigate how these two unrelated species that have lived together and are thought to have coevolved social cognition [ 24 ], are able to influence [ 18 ] and perceive each other [ 25 ]. Furthermore, because animal FACS are built within a comparative framework, it is possible to compare facial repertoires across species; a comparison of EquiFACS and ChimpFACS demonstrated that horses have a larger potentiality for movement than chimpanzees [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In behavioral studies of domestic dogs, however, the challenges arise not from a paucity of characterization, but from a surfeit of it. A focus of majority of early dog behavior studies have been on subjective rating scales – although new research has seen increased use of quantitative variables ( Gerencsér et al, 2013 ; Huber, 2013 ; Correia-Caeiro et al, 2020 ). Most of these rating scales categorize dog behavior into “prosocial” and “reactive” categories.…”
Section: Introductionmentioning
confidence: 99%